PARTISIPASI MASYARAKAT PANCAROBA TERHADAP KEBIJAKAN TRANSPARANSI PENGEOAAN DANA DESA - Arjon, Viktorianus Marterik; Syamsuri, Syamsuri; Atmaja, Thomy Sastra; Dewantara, Jagad Aditya; Zakso, Amrazi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This Study Aims To Determine The Participation Of The Pancaroba Community In The Transparency Poicy For Managing Viage Funds. The Genera Probem In This Study Is How The Community Participates In The Impementation Of Viage Fund Management, How Transparency Of Viage Fund Management Is Carried Out In Pancaroba Viage, And The Obstaces And Soutions Faced By The Pancaroba Viage Government In Managing Viage Funds. The Research Method Used Is Descriptive With A Quaitative Approach. Data Coection Techniques Used Incuded Observation Guides, Interview Guides, And Documentation. The Anaysis In This Study Was Presented In A Quaitative, Descriptive Manner Using Seven Informants From The Pancaroba Viage Community. The Resuts Of This Study Show That The Community In Pancaroba Viage Participates In Everything From Panning Meetings To Deveopment Supervision. The Impementation Of Transparency In The Management Of Funds In Pancaroba Viage Is Quite Good Because It Is Impemented Openy, Providing Information Regarding The Use Of Viage Funds, Whether It Is The Design Of The Aocation Of Funds In Each Program. Through Viage Meetings And Information Boards Posted In Front Of The Viage Office. In Managing Viage Funds, It Shows That The Management Of Funds In Pancaroba Viage Has Probems In Disbursing Funds, Namey Deays In Disbursing Funds. The Soution Carried Out By The Pancaroba Viage Government Is To Coordinate With Parties In The District By Asking Questions Regarding Disbursement Of Funds And Showing The Resuts Of Accountabiity Reports To The District.